Estimation of serum leptin in female patients with nodal osteoarthritis - Hashim, Raid D.; Turki, Kismat M.; Alosami, Mohammed H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Nodal osteoarthritis is one of the most common arthropathy worldwide, the etiology is uncertain but many biochemical markers are recognized. Many studies have shown that leptin might have a role in the pathogenesis of osteoarthritis, but little is known about the relation between serum leptin and nodal osteoarthritis. Subjects and method: 52 women with nodal osteoarthritis and 40 apparently healthy women as a control were included in the study; serum leptin was measured in all subjects. Student t-test was applied to find out the significance of difference in the mean v Results: There was a significant difference in the mean of serum leptin between patients and control groups. Conclusion: the results of the current study suggest that leptin might have a role in the pathogenesis of nodal osteoarthritis